Observation of oscillations of atmospheric neutrinos with the IceCube Neutrino Observatory - Euler, Sebastian (2014)
Neutrino oscillations have become one of the most important research topics in particle physics since their discovery 15 years ago. In the past, the study of neutrino oscillations has been largely the domain of dedicated experiments, but in the last year also the large-volume neutrino telescopes ANTARES and IceCube reported their results on the oscillations of atmospheric muon neutrinos and thus joined the community of experiments studying neutrino oscillations. The precision of their results is not yet competitive, but their sheer size and the consequently enormous statistics give rise to the expectation of a competitive measurement in the future. This thesis describes an analysis that was done on IceCube data taken with the nearly complete detector in the years 2010/2011. IceCube is the world's largest neutrino detector, located at the geographic South Pole, where it uses the Antarctic ice sheet as its detection medium. It detects neutrinos interacting within or close to the instrumented volume by observing the Cherenkov light which is emitted by secondary particles produced in these interactions. An array of optical sensors deployed within a cubic kilometer of ice detects the Cherenkov light and makes it possible to reconstruct the energy and direction of the initial neutrino. Unfortunately, IceCube detects not only neutrinos: the desired neutrino signal is buried in a huge background of atmospheric muons, produced in air showers induced by cosmic rays. This background has to be rejected first. The analysis presented here employs an event selection that is based on the idea of using the outer layers of IceCube as an active veto against the background of atmospheric muons and achieves the necessary background rejection of more than 6 orders of magnitude while keeping a high-statistics sample of several thousands of muon neutrinos. In contrast to the earlier IceCube analysis, which used only the zenith angle, it then performs a 2-dimensional likelihood fit on reconstructed zenith angle and energy and improves ...